2020
DOI: 10.32598/cjns.6.22.4
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life of Mothers of Children With Phenylketonuria

Abstract: Background: Quality of life is one of the pivotal notions of the World Health Organization’s perspective. Regarding the complications of Phenylketonuria (PKU) disease in children, it seems that this disease affects the quality of life of these mothers. Objectives: Investigating the quality of life of mothers with PKU children and to compare it with that of mothers of normal children. Materials & Methods: This case-control study was conducted on 65 mothers with PKU children and 122 mothers with normal child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…With such a high stress and difficulties arising from caring children with PKU, it not only affects the psychological state of the caregivers, but it greatly affects the HRQOL of caregivers most importantly mothers, as they are the primary caretakers. 39 The overall PHRQOL was poor in caregivers of children and adolescents with PKU. It was reported that lowest level of QOL was found in "self-development" domain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With such a high stress and difficulties arising from caring children with PKU, it not only affects the psychological state of the caregivers, but it greatly affects the HRQOL of caregivers most importantly mothers, as they are the primary caretakers. 39 The overall PHRQOL was poor in caregivers of children and adolescents with PKU. It was reported that lowest level of QOL was found in "self-development" domain.…”
Section: Discussionmentioning
confidence: 99%
“…With such a high stress and difficulties arising from caring children with PKU, it not only affects the psychological state of the caregivers, but it greatly affects the HRQOL of caregivers most importantly mothers, as they are the primary caretakers. 39…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the psychometric assessment of the questionnaire (validity and reliability) confirmed other studies. In Mortazavi and colleagues' study (24), the content validity rate, intraclass correlation coefficient, and Cronbach's alpha values were calculated to be 0.93, 0.97, and 0.84, respectively.…”
Section: Women's Social Participation Factors Questionnairementioning
confidence: 99%